Parameter Optimization Considering the Variations Both from Materials and Process: A Case Study of Scutellaria baicalensis Extract - Xuecan Zhang; Zhilong Tang; Bo Chen; Xingchu Gong (Separations)
The Quality by Design (QbD) concept has been widely applied to the optimization of traditional Chinese medicine production processes recently. This work focused on optimizing the critical purification process of Scutellaria baicalensis extract used in the preparation of Zhusheyong Shuanghuanglian. Considering the impact of noise parameters and changes in herbal properties, an experimental design method was employed for optimization. Multiple batches of Scutellaria baicalensis decoction were prepared in this research, and quantitative models of Scutellaria baicalensis herbal properties, critical process parameters (CPPs), and process evaluation indicators were established. The R2 of the quantitative models were all higher than 0.80. According to the model, the yield of baicalin was identified as a critical material property (CMA). The pH of first acid precipitation (X1), first temperature holding time (X2), pH of alkalization (X3), ethanol amount (X4), and end pH of ethanol washing (X5) were CPPs. Considering the difficulty in controlling the end pH of the ethanol washing, it was considered to be a noise parameter. The Monte Carlo probability-based method was used to calculate the design space, determining the range of controllable parameters, which was successfully validated through experiments. Normal operation ranges for controllable parameters are recommended as follows: X1 of 0.8–2.2, X2 of 25–35 min, X3 of 6.5–7.5, and X4 of 0.8–1.2 g/g.